Kinerja Dinas Lingkungan Hidup dalam Mengelola Sampah di Kecamatan Rantau Utara Kabupaten Labuhanbatu - Elsya Sonia; Siti Hazzah Nur Ritonga (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2024)
This research aims and explains the performance of the Environmental Service in Managing Waste in Rantau Utara District, Labuhanbatu Regency. The research method used in this study is qualitative research with a descriptive nature, with data collection techniques of direct observation, in-depth interviews, and detailed document analysis. This research was conducted at the Labuhanbatu Regency Environmental Service. The research informants consisted of the Head of Department, Head of waste management, waste management staff, cleaning staff, the community and school children. The research results show that the performance of the Labuhanbatu Regency Environmental Service in providing services is quite good in managing waste accumulation in the area. In terms of indicator 1) Productivity in recycling waste management, organic and inorganic waste has economic value, but in terms of human resources there is still a shortage of staff. 2) The quality of service is quite good in waste pickup but still faces challenges related to inadequate facilities. 3) Responsiveness, the department has responded to community complaints and provided outreach to the community. 4) Responsibility in this case the department has carried out its duties and responsibilities in accordance with its main duties and functions. 5) The Accountability Service has implemented its policies and activities with procedures, they have monitored and controlled the waste management process on a regular basis. Efforts continue to be made to overcome this problem.